A French cipher from the late 19th century. Issue 4 (4th July 2021) - Géraud-Stewart, Rémi; Naccache, David
Abstract: The Franco-Prussian war (1870–1871) was the first major European conflict during which extensive telegraph use enabled fast communication across large distances. Field officers would therefore have to learn how to use secret codes. But training officers also raises the probability that defectors would reveal these codes to the enemy. Practically all known secret codes at the time could be broken if the enemy knew how they worked. Under Kerckhoffs' impulsion, the French military thus developed new codes, meant to resist even if the adversary knew the encoding and decoding algorithms, that were simple enough to be explained and taught to military personnel. Many of these codes were lost to history. One of the designs however, due to Major H. D. Josse, has been recovered and this article describes the features, history, and role of this particular construction. Josse's code was considered for field deployment and underwent some experimental tests in the late 1800 s, the result of which were condensed in a short handwritten report. During World War II, German forces got hold of documents describing Josse's work, and brought them to Berlin to be analyzed. A few years later these documents moved to Russia, where they have resided since.